(untitled) (Global Journal of Human-Social Science, 2023)
The future has become the central time of Anthropocene due to multiple factors like climate crisis emergence war and COVID times As a social construction time brings a diversity of meanings measures and concepts permeating all human relations The concept of time can be studies in a variety of fields but in Social Psychology time is the bond for all social relations To understand Imaginable Futures as narratives that permeate human relations requires the discussion of how individuals are imagining anticipating and expecting the future According to Kable et al 2021 imagining future events activates two brain networks One which focuses on creating the new event within imagination whereas the other evaluates whether the event is positive or negative To further investigate this process a survey with 40 questions was elaborated and applied to 312 individuals across all continents The results show a relevant rupture between individual and global futures Data also demonstrates that the future is an important asset of the now and participants are not so optimistic about it It is possible to notice a growing preoccupation with the global future and the uses of technology